A novel and cost-effective model to screen and treat cervical cancer and precancers at the point of care - Bouquet, Jean M.; Morris, Emily; Zapata, Isain (Frontiers in Public Health, 2025)
BackgroundCervical cancer has a high incidence to high mortality rate and poses an important global burden that disproportionately affects women in underdeveloped areas of the world. The World Health Organization has proposed a new and ambitious policy that aims to reduce the number of deaths from cervical cancer by 62.6 million over the next 70 years. However, there are many obstacles to the adoption of this policy and implementation in both Resource-Rich and Resource-Constrained Countries.MethodsIn this perspective article, we propose a cost-effective, sustainable, and practical model that introduces a kit that may help overcome some of the existing barriers and achieve the goal to eventually eliminate cervical cancer. The kit includes a novel vaginal speculum that provides better visibility of the cervix, ease-of-use, and patient comfort; AI-assisted cervicography with a portable colposcope or Smart Phone; and canister-based cryotherapy.ResultsPrevious studies in Peru, Panama, Paraguay, and Kenya have demonstrated that these kits represent a novel, cost-effective, practical, accurate, and sustainable model to screen, triage, and treat cervical cancer and precancers at the point of care anywhere in the world.ConclusionThis model is a simple and inexpensive solution to some of the barriers to care for cervical health, potentially providing significant benefits by decreasing morbidity and mortality of cervical cancer without significant risk for women throughout the world.